PENGARUH PENDAPATAN BUNGA PINJAMAN TERHADAP PROFITABILITAS KOPERASI PADA KSP KOPDIT PINTU AIR CABANG BAJAWA - Sri Rejeki, Eka; Maria Diliana, Siktania; Lewar, Maria Viviana Nurak (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of the study was to determine the effect of loan interest income on profitability at KSP Kopdit Pintu Air Bajawa Branch. The type of research used in this study is a type of quantitative research with a causal associative approach method, the population used in this study is the financial statements at the KSP Kopdit Pintu Air Bajawa Branch. The samples used in this study were the remaining report of business results and the balance sheet report. The data analysis technique used in this study is a simple linear regression analysis with the tests used are descriptive statistical tests and inferential statistical tests, namely classical assumption tests, hypothesis tests, and determination coefficient tests. Data analysis was carried out using the Statistical Package for the Social Science (SPSS) program version 20. The results of this study show that the insignificance value of the variable loan interest income (X) is greater than the specified significance level of 0.05 (0.146> 0.05), thus it can be concluded that there is no influence between loan interest income (X) and cooperative profitability (Y).